2020
DOI: 10.1097/bsd.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Mitigate Industry Influence in Industry Sponsored Research

Abstract: Medical and surgical research has always had a longstanding relationship with industry-based funding from sources, such as drug and device companies. Concerns exist surrounding the association between funding sources, outcome from studies and publication bias. Studies demonstrating increased odds ratios associated with positive results in industry sponsored studies across medicine have stimulated Cochrane reviews, literature reviews and other articles to examine this relationship further. In spine surgery in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“… 9 Industry-sponsored research can benefit the field of spine surgery, but it can also bias both publication of results as well as presentation of data and its interpretation. 16 In general, industry-sponsored research is associated with more favorable efficacy results, more favorable study conclusions, and lower agreement between study results and conclusions when compared to non–industry-funded research. 17 The physician tasked with interpreting and applying clinical research to treatment decisions must be aware of these associations.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Industry-sponsored research can benefit the field of spine surgery, but it can also bias both publication of results as well as presentation of data and its interpretation. 16 In general, industry-sponsored research is associated with more favorable efficacy results, more favorable study conclusions, and lower agreement between study results and conclusions when compared to non–industry-funded research. 17 The physician tasked with interpreting and applying clinical research to treatment decisions must be aware of these associations.…”
Section: Discussionmentioning
confidence: 99%
“…publication bias). 7 , 24 , 25 , 26 Misappropriation and malevolence arising from various partnerships have sometimes eroded public trust in research. 27 There has also been notable gender disparity in AIPs, where female physicians in some fields have received fewer and lower industry payments.…”
Section: Introductionmentioning
confidence: 99%
“…Fostering functional ties of health care providers to industry for the greater good has clearly shown itself to be a major driver for positive advances in health care. 1 Due to the dimension of financial incentives attainable and the potential for major adverse effects on patient health and well-being of health care systems some regulatory oversight is obviously desirable. Aside from blatant fraudulent intent, perhaps one of the most underrecognized aspects of commercially funded studies is a confirmation bias as shown in the significantly higher propensity for reporting positive outcomes with industry sponsored studies compared to nonfunded studies (78.9% vs 63.3% in one study and 98 vs 88% in another).…”
mentioning
confidence: 99%
“… 2 , 3 Of course, author bias from direct commercial interests remains one of the most prevalent concerns in a lucrative field like Spine surgery as shown repeatedly over the last 30 years. 1 In general, we sadly have to assume that there is a continued strong and persistent underreporting of financial relationships with industrial entities despite near ubiquitous requests for declaration of conflicts of interest. In a recent study of 5070 articles in Orthopaedic and General surgery Trauma literature only 16.6% of authors disclosed their financial conflicts correctly, with 26.3% of Orthopaedic Surgeons and only 4.8% of General surgeons disclosing their conflicts as requested.…”
mentioning
confidence: 99%
See 1 more Smart Citation